PPG Students’ Perceptions of Digital Authentic Assessment Development in Language Learning: A Growth Mindset Perspective - Ayu Azzura Aulia; Zahra Alya Suresh; Rio Rinaldi (Darul Yasin Al Sys, 2026)
Although digital authentic assessment has attracted increasing attention in educational research, limited evidence exists regarding pre-service teachers’ perceptions of its development in language learning from a growth mindset perspective. This study aimed to examine the perceptions of Professional Teacher Education students at the Faculty of Teacher Training and Education, Bung Hatta University, toward the development of digital authentic assessment in language learning through the lens of growth mindset. A quantitative descriptive survey design was employed, involving all 30 students enrolled in the Growth Mindset course through total sampling. Data were collected using a Likert-scale questionnaire comprising ten positively worded statements covering understanding of digital authentic assessment, creativity in assessment development, digital competence, feedback effectiveness, learning motivation, and intention to implement digital assessment practices. The data were analyzed using descriptive statistical techniques. The findings showed that 29 participants strongly agreed and one participant agreed with the measured indicators, demonstrating highly positive perceptions of digital authentic assessment in language learning. Participants viewed this form of assessment as relevant to the demands of 21st-century education, capable of enhancing creativity and assessment effectiveness, and supportive of the comprehensive development of learners’ language skills. The study concludes that digital authentic assessment has substantial potential to foster innovative and adaptive language-learning environments. These findings extend the literature on growth mindset and technology-integrated assessment in teacher education and highlight the need for teacher education institutions to strengthen pre-service teachers’ digital competencies and systematically integrate technology-based authentic assessment into professional training programs. Further research should examine its implementation and effectiveness across broader educational settings and larger populations.